A rapid review of educational preparedness of advanced clinical practitioners. (8th August 2019) - Dover, Nicola; Lee, Geraldine A.; Raleigh, Mary; Baker, Edward J.; Starodub, Roksolana; Bench, Suzanne; Garry, Brendan
Abstract: Aim: The aim of this study was to synthesize available data on current educational provision related to preparation for the advanced clinical practice role. Design: A mixed methods rapid review of the literature. Data Sources: A search of Ovid Medline and Ovid EMBASE for English language papers published 2006–2018 resulted in 38 publications, which met the criteria for inclusion. Review Methods: Using Tricco's seven‐stage process, following an identification of relevant papers and data extraction, a data‐based convergent synthesis was used to convert quantitative papers into qualitative data prior to completing a narrative synthesis. Results: The four themes identified from data synthesis were consolidation; theory to practice gap; competency and mentoring. A lack of preparedness for new advanced clinical practitioners completing an educational programme was noted with a need identified for a clinically focussed consolidation period to enable practitioners to develop their skills under supervision in the clinical environment. Conclusion: As the needs for different models of health care evolve with the expansion of advanced practice, appropriate education and clinical supervision are important aspects in the delivery of programmes that allow individuals to be competent and confident practitioners providing safe and effective health care. Impact: There is a paucity of papers on educational preparedness of advanced clinical practitioners. Our findings demonstrate a lack of preparedness and the need for a clinically focussed consolidation period with good role models and mentors following completion of a Master's programme. Employers and higher education institutions need to ensure a protected period of time is available for newly qualified advanced clinical practitioners to allow consolidation of clinical practice. Abstract : 目的: 本研究的目的是对当前涉及高级临床实践角色准备的相关可用教育准备数据进行总结。 设计: 采用混合研究法, 对文献进行快速评价。 资料来源: 对Ovid Medline和Ovid EMBASE上2006年至2018年发表的英文论文进行了检索, 结果有38篇符合纳入标准。 综述方法: 采用Tricco的七阶段流程, 在确定相关论文和提取数据后, 采用基于数据的汇集式总结方法将定量论文转化为定性数据, 然后, 完成叙述性总结。 结果: 从数据总结中确定的四个主题是:巩固;理论与实践之间的差距;能力与指导。有人指出, 新的高级临床医师在完成教育方案这一方面准备不足, 需要有一个专注临床的巩固期, 使他们能够在临床环境的监督下发展自己的技能。 结论: 随着高级实践范围的扩展, 对不同医护服务模式的需求也在不断变化, 适当的教育和临床监督是提供方案的重要方面, 如此才足以使个人能够胜任且自信地提供安全、有效的医护服务。 影响: 关于高级临床医师教育准备方面的论文很少。我们的调查结果表明, 在完成硕士课程后, 缺乏准备, 而且, 存在对专注临床的巩固期与良好的榜样和导师的需求。用人单位和高等教育机构需要确保为新获得资格的高级临床医师提供一段保护期, 以便对临床实践进行巩固。